Adjustable laptop table with DIY concept / Zamri Buhari, Nur Hannnani Abd Latif and Shaikh Abdul Karim Yamani Zakaria - Buhari, Zamri; Abd Latif, Nur Hannnani; Zakaria, Shaikh Abdul Karim Yamani (2012)
Furniture plays an imperative role in completing human lifetime, as they been widely used, anywhere and at anytime. Functions, design, space, price and material used to build up the furniture were an important features need to be considered by customers. High price and lack of space are some limitations that faced by students at hostel or other customers that live in a small house in buying furniture. This study is conducted to overcome those problem by designing a adjustable laptop table with "do it yourself" (DIY) concept for ease of handling and portability, and at economical price. A laptop table is combined with an adjustable book shelves cabinet. Modern and contemporary design were applied to sui t with the lifestyle of modern human Iiving. Laminated particleboard and blockboard were used as main material.